Spatial-temporal variability of aerosol sources based on chemical composition and particle number size distributions in an urban settlement influenced by metallurgical industry - Pokorná, Petra; Leoni, Cecilia; Schwarz, Jaroslav; Ondráček, Jakub; Ondráčková, Lucie; Vodička, Petr; Zíková, Naděžda; Moravec, Pavel; Bendl, Jan; Klán, Miroslav; Hovorka, Jan; Zhao, Yongjing; et al. (Environmental science and pollution research international, 2020)
The Moravian-Silesian region of the Czech Republic with its capital city Ostrava is a European air pollution hot spot for airborne particulate matter (PM). Therefore, the spatiotemporal variability assessment of source contributions to aerosol particles is essential for the successful abatement strategies implementation. Positive Matrix Factorization (PMF) was applied to highly-time resolved PM0.15-1.15 chemical composition (1 h resolution) and particle number size distribution (PNSD, 14 nm - 10 μm) data measured at the suburban (Ostrava-Plesná) and urban (Ostrava-Radvanice) residential receptor sites in parallel during an intensive winter campaign. Diel patterns, meteorological variables, inorganic and organic markers, and associations between the chemical composition factors and PNSD factors were used to identify the pollution sources and their origins (local, urban agglomeration and regional). The source apportionment analysis resolved six and four PM0.15-1.15 sources in Plesná and Radvanice, respectively. In Plesná, local residential combustion sources (coal and biomass combustion) followed by regional combustion sources (residential heating, metallurgical industry) were the main contributors to PM0.15-1.15. In Radvanice, local residential combustion and the metallurgical industry were the most important PM0.15-1.15 sources. Aitken and accumulation mode particles emitted by local residential combustion sources along with common urban sources (residential heating, industry and traffic) were the main contributors to the particle number concentration (PNC) in Plesná. Additionally, accumulation mode particles from local residential combustion sources and regional pollution dominated the particle volume concentration (PVC). In Radvanice, local industrial sources were the major contributors to PNC and local coal combustion was the main contributor to PVC. The source apportionment results from the complementary datasets elucidated the relevance of highly time-resolved parallel measurements at both receptor sites given the specific meteorological conditions produced by the regional orography. These results are in agreement with our previous studies conducted at this site. Graphical abstract.
Keywords: velikost částic; aerosoly; Cities; Elemental composition; monitorování životního prostředí; Particle Size; velkoměsta; Nanoparticles; znečištění ovzduší; Air Pollution; Metallurgical industry; Local heating; Particulate Matter; Highly time-resolved parallel measurements; Aerosols; Air Pollutants; Czech Republic; Environmental Monitoring; Česká republika; Regional transport; látky znečišťující vzduch; pevné částice